INISIASI PENGEMBANGAN DESA SIAGA DONOR DARAH MELALUI PROGRAM PEMERIKSAAN DAN PENDATAAN GOLONGAN DARAH WARGA DUSUN KALIADEM, SLEMAN, YOGYAKARTA - Kumara Rahmawati Zain; Wiwit Sepvianti; Aulia Rahman; Gravinda Widyaswara; Arif Tirtana (Jurnal Abdi Insani, 2023)
Alert village is a concept of empowerment and community participation at the village level, accompanied by the development of alertness and readiness of the community to maintain their health independently. Residents of Alert Village have the readiness of resources and the ability and willingness to independently prevent and overcome health problems, disasters and health emergencies. The blood donor alert village is expected to be able to accommodate health problems that arise in areas prone to natural disasters, if during a disaster there is the possibility of the route being cut off. The concept of Desa Siaga Donor is to build a system in a village that is responsible for maintaining community health at the village level, it is hoped that it will overcome problems related to maternal mortality so that it can be accommodated, especially those related to meeting the need for blood during childbirth. Collecting residents' blood type data as an initiation of the Village Alert Program for blood donors in Dusun Kaliadem, especially in fulfilling the need for blood during the delivery process. Community service through the Blood Donor Alert Village initiation activity in Kaliadem Hamlet, Kepuharjo Village, Cangkringan District, Sleman Regency involving 14 DIII students of Blood Bank Technology STIKes Guna Bangsa Yogyakarta by running the Donor Alert Village Initiation program. The total number of residents of Kaliadem Hamlet is 215 people, of which 48.83% have their blood type recorded while 51.16% are not recorded. The community empowerment program in Kaliadem Hamlet, Kepuharjo Village, Cangkringan District, Sleman Regency was carried out as part of the Blood Donor Alert Village Initiation Effort by carrying out health education activities as well as data collection and examination of people's blood groups in Kaliadem Hamlet. Based on the results of blood group checking, it was found that 34 residents had blood type A, 30 residents had blood type B, 5 residents had blood type AB and 36 residents had blood type O. Blood checking data for Kaliadem Hamlet residents will be the main data in the Donor Alert Village initiation. The blood group data of Kaliadem Hamlet residents then becomes part of the Kepuharjo Village database.